Melatih Anggota Keltan Rambutan dan Keltan Sakato Kota Padang untuk Mengendalikan Wereng Batang Coklat (WBC) dengan Joint Predator - Sandra Desiska; My Syahrawati; Arneti Arneti; Zurai Resti; Martinius Martinius; Haliatur Rahma; Eri Sulyanti; Tre Julia Nasral; Ryan Hidayat (Warta Pengabdian Andalas, 2019)
The attacks of brown planthopper or BPH (Nilaparvata lugens) in West Sumatra have been recorded since 2012 and continued to increase throughout 2015-2017. Wolf spider (Pardosa pseudoannulata) and lady beetle (Verania lineata) are two predators that can be used as natural enemies. Some research reports that the wolf spider can consume the BPH as much as 5-15 individuals while lady beetles consume as much as 1-11 individuals per day. Training on the use of two predators was carried out in farmer group of Rambutan, Kelurahan Bungus Barat and farmer group of Sakato Kelurahan Lambung Bukit, Padang City. The training aimed to show to farmers the predation rate of both predators against ten individuals of BPH provided. The treatment consisted of the predation rate of both predators (1 individual of wolf spider, 1 individual of lady beetle, 1: 3 composition of the joint predator) in 3 replications. All wolf spiders, lady beetles and BPH used were collected from rice field in Pauh District, Padang City. Within one hour, joint predators in Rambutan were able to consume 53% of the BPH provided, while joint predators in Sakato were able to consume 43%. Some efforts from farmers are needed to protect and conserve the presence of two predators so that they can act as natural enemies in the field.